Harold Wagner. Meaning – Quest for Meaning – Meaning of Life (II) - Wagner, Harold (Acta Paedagogica Vilnensia, 2007)
Philosophy and theology are the disciplines that contribute to the solution of the question of meaning. The arguments in these disciplines are very abstract and remote from the everyday life. However, finally both these disciplines must provide answers to human everyday life. This second essay introduces the argumentation level of both of these disciplines in order to supply the foundations and justification for the further considerations of the meaning of human life.